2022
DOI: 10.1002/bab.2336
|View full text |Cite
|
Sign up to set email alerts
|

Monascin and ankaflavin—Biosynthesis from Monascus purpureus, production methods, pharmacological properties: A review

Abstract: Monascus purpureus copiously yields beneficial secondary metabolites , including Monascus pigments, which are broadly used as food additives, as a nitrite substitute in meat products, and as a colorant in the food industry. Monascus yellow pigments (monascin and ankaflavin) have shown potential antidiabetic, antibacterial, anti-inflammatory, antidepressant, antibiotic, anticancer, and antiobesity activities. Cosmetic and textile industries are other areas where it has established its potential as a dye. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Further studies were conducted on the mineral component in whey related to monascin production by M. ruber NBRC 32318. Although many studies on the effect of minerals on Monascus yellow pigment production have been conducted using spectrophotometric analysis, 12,13,27 few studies have been concerned with specific monascin production analysis. Lung et al 33 have reported that the addition of Mg, Ca, Zn, or Fe to water increased monascin production when dioscorea was subjected to solid-state fermentation with M. purpureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies were conducted on the mineral component in whey related to monascin production by M. ruber NBRC 32318. Although many studies on the effect of minerals on Monascus yellow pigment production have been conducted using spectrophotometric analysis, 12,13,27 few studies have been concerned with specific monascin production analysis. Lung et al 33 have reported that the addition of Mg, Ca, Zn, or Fe to water increased monascin production when dioscorea was subjected to solid-state fermentation with M. purpureus.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although a review by Feng has shown that filamentous fungi can produce more abundant secondary metabolites on solid culture than liquid culture, 11 liquid culture is frequently used due to its flexible applicability to the regulation of culture conditions. 12,13 Many parameters, including carbon and nitrogen sources, pH, temperature, and aeration, affect secondary metabolite production. Accordingly, a synthetic medium is a convenient method for establishing the ideal composition and identifying crucial factors for secondary metabolite production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monascin is a yellow natural pigment formed by the cultivation and fermentation of Monascus ruber in cereals under certain conditions, which can reduce blood lipid and blood pressure and has anti-inflammatory and antioxidant effects (66). Monascin has been shown to play a role in endogenous hematoma absorption as a natural dual agonist of Nrf2 and PPAR-γ.…”
Section: Monascinmentioning
confidence: 99%
“…In case of food, biscuits made from fermented soybean meal had better nutritional (fibre and lipid) and functional (isoflavones and antioxidant activity) properties (Silva et al, 2018). Monascus pigment can also be extracted from fermented soybean meal, which is widely used in the food industry as food additives (Keivani et al, 2020;Adin et al, 2022). Besides, Bacillus species extracted from traditional fermented foods were applied to soybean meal to produce new bioactive peptides, which could be used as nutritional products (Kumari et al, 2023).…”
Section: Application Of Fermented Soybean Mealmentioning
confidence: 99%